Performance of aerobic granular sludge in treating soy sauce wastewater at different hydraulic retention time - Harun, Hasnida; A. Hamid, Hazren; Mohamed Sunar, Norshuhaila; Ahmad, Faridahanim; Nor Anuar, Aznah; Rosman, Noor Hasyimah; Othman, Inawati (Science Publishing Corporation, 2018)
Aerobic granular sludge had shown its capability in treating soy sauce wastewater, but its reactor performance, granules properties and biokinetics in different hydraulic retention times (HRT) is still unknown. To ensure the reactor is performed in optimum condition, a judicially selection of HRT is important. The study was conducted in a high and slender column operated according to a sequential batch reactor (SBR) with a sequence of aerobic and anaerobic/anoxic reaction phases. Three different HRTs (8, 16, 24 h) and different anaerobic and aerobic reaction time were evaluated. In the study demonstrated the increase in HRT could reduce the organic loading rate (OLR) as well as biomass yield (Yobs, Y), endogenous decay rate (kd) and overall specific biomass growth rate (µoverall). It was observed a slight increase in the mixed liquor suspended solid (MLSS) and the granules mean size as the OLR decreased. Meanwhile, in the lowest HRT reactor, a narrow diameter range of aerobic granule from 3 to 100 µm was observed due to the development of small and dense granules. The HRT of 24h with aerobic and anaerobic/anoxic reaction time of 3.88 and 7.77h respectively is the SBR’s best performances due to the improvement of the aerobic granular physical properties